First record of the tribe Phlepsiini (Hemiptera: Cicadellidae: Deltocephalinae) from China, with description a new genus and species - Dai, Ren-Huai; Qu, Ling; Yang, Mao-Fa (Zootaxa, 2016)
The tribe Phlepsiini Zahniser & Dietrich, 2013 is reported from China for the first time based on a new genus and species, Brevivalvala melanosticta gen. et sp. nov., here described and illustrated from Yunnan Province. This new genus can be distinguished from other genera in this tribe by the short valve and subgenital plate without macrosetae.